Corrosion Inhibition Efficiency and Adsorption of Azo Schiff Base Chelate Surfactant at Carbon Steel in Hydrochloric Acid Interface - Mohammed Abdulhussin Enad (Journal of Global Pharma Technology, 2020)
The aromatic Schiff base with azo linkage (CHMB) has been synthesized and characterized by FT-IR, 1H NMR and 13C NMR spectroscopic techniques. The compound (CHMB) has been evaluated as carbon steel corrosion inhibitor at different concentrations (0.1, 0.5, 1 and 5 mM) and different temperatures (298-318 K). The corrosion inhibition efficiency was studied by Potentiodynamic polarization. The effects of concentration and temperature on the inhibition efficiency were studied by Potentiodynamic polarization measurements, the results showed that increasing concentration of (CHMB) increases the inhibition efficiency while increasing the temperature decreases it, the highest corrosion inhibition efficiency, 93.58% was recorded with 5 mM of CHMB at 298 K in 1 M HCl. The adsorption process was found to obey Langmuir isotherm, and the adsorption thermodynamic parameters were studied.Keywords: Carbon steel, Corrosion inhibitors, Azo, Schiff base, Organic inhibitors.